Persepsi Peserta Didik Terhadap Guru Bimbingan dan Konseling di Madrasah Aliyah Ali Maksum - Laelatul Badriah (At-Tajdid: Jurnal Ilmu Tarbiyah, 2018)
This study examines students' perceptions of counseling counseling held in Madarasah Aliyah, this study is conducted on the basis of the assumption of guidance and counseling teachers (BK) is a teacher to watch out for, unpleasant teachers, scary teachers, services provided BK services for students with problems, services as a form of student therapy, and learners judge that whoever is included in the record of BK teachers are naughty and troubled learners. This research is a field research using qualitative approach. The research saboh is the female students and the BK teacher. Data were collected using interviews, documentation, and observation and data validity using triangulation and analyzed by using qualitative descriptive analysis. The results of the study showed the perception of learners of guidance and counseling teachers welcome and positive. BK Teachers can act as understanding, prevention, maintenance, development, and poverty alleviation. And able to provide orientation services, information services, placement services, counseling services, group guidance services, and group counseling services.